Biochemical mechanisms of aggregation in TGFBI-linked corneal dystrophies. (July 2020) - Nielsen, Nadia Sukusu; Poulsen, Ebbe Toftgaard; Lukassen, Marie V.; Chao Shern, Connie; Mogensen, Emilie Hage; Weberskov, Christian E.; DeDionisio, Larry; Schauser, Leif; Moore, Tara C.B.; Otzen, Daniel E.; Hjortdal, Jesper; Enghild, Jan J.
Abstract: Transforming growth factor-β-induced protein (TGFBIp), an extracellular matrix protein, is the second most abundant protein in the corneal stroma. In this review, we summarize the current knowledge concerning the expression, molecular structure, binding partners, and functions of human TGFBIp. To date, 74 mutations in the transforming growth factor-β-induced gene ( TGFBI ) are associated with amyloid and amorphous protein deposition in TGFBI -linked corneal dystrophies. We discuss the current understanding of the biochemical mechanisms of TGFBI -linked corneal dystrophies and propose that mutations leading to granular corneal dystrophy (GCD) decrease the solubility of TGFBIp and affect the interactions between TGFBIp and components of the corneal stroma, whereas mutations associated with lattice corneal dystrophy (LCD) lead to a destabilization of the protein that disrupts proteolytic turnover, especially by the serine protease HtrA1. Future research should focus on TGFBIp function in the cornea, confirmation of the biochemical mechanisms in vivo, and the development of disease models. Future therapies for TGFBI -linked corneal dystrophies might include topical agents that regulate protein aggregation or gene therapy that targets the mutant allele by CRISPR/Cas9 technology. Highlights: TGFBIp is highly abundant in the cornea. 74 mutations in the TGFBI gene are associated with TGFBI- linked corneal dystrophies. A change in TGFBIp solubility, stability, and proteolytic processing is linked to TGFBIp deposition. Genome editing using CRISPR/Cas9 can be a future treatment strategy.